2010
DOI: 10.1016/j.ejvs.2009.12.025
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Different Concentrations of Sodium Tetradecyl Sulphate and Initial Balloon Denudation on Endothelial Cell Loss and Tunica Media Injury in a Model of Foam Sclerotherapy

Abstract: Balloon denudation increased ECL but did not facilitate tunica media injury. Equivalent injury was inflicted by 1% and 3% STD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
4
14
1
Order By: Relevance
“…Hamel-Desnos et al 9 reported in a functional in-vivo study that there was no statistically significant difference between the clinical success rates of 1% and 3% polidocanol foam after a 2-year followup. Similar results were also noted by Ikponmwosa et al 12 Our data mainly agree with those of Ikponmwosa et al and Hamel-Desnos et al in indicating that the effectiveness of foam sclerotherapy is independent of the concentration used, as even the lowest concentration led to significant damage to the vein wall. It is also worth mentioning that our study demonstrated 1% foam sclerosant to be the most effective concentration in terms of the pathological damage it exerted, compared to the higher doses of 2% and 3%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hamel-Desnos et al 9 reported in a functional in-vivo study that there was no statistically significant difference between the clinical success rates of 1% and 3% polidocanol foam after a 2-year followup. Similar results were also noted by Ikponmwosa et al 12 Our data mainly agree with those of Ikponmwosa et al and Hamel-Desnos et al in indicating that the effectiveness of foam sclerotherapy is independent of the concentration used, as even the lowest concentration led to significant damage to the vein wall. It is also worth mentioning that our study demonstrated 1% foam sclerosant to be the most effective concentration in terms of the pathological damage it exerted, compared to the higher doses of 2% and 3%.…”
Section: Discussionsupporting
confidence: 93%
“…The saphena sections taken after 15 min showed larger areas of necrosis, also involving tunica media, and after 30 min early venous sclerosis, early parietal cover and shrinkage of the lumen were seen. However, these histological changes represent not only the effects of foam sclerosant but also the liquid form, since Ikponmwosa et al 12 realized that foam sclerosant couldn't remain stable and completely reverted to liquid form within 300 s. Similarly, in our study, we realized that the foam completely reverted to liquid in a given amount of time for each concentration, and set the contact time of the experiment accordingly. In the study of Orsini and Brotto, histopathological changes seen at 15 and 30 min represented the cumulative effect of foam sclerosant and mostly the reverted liquid form without any foam left.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Due to the small volume, these microvessels have no hemodynamic or clinical relevance in this case. 7 Our observations thus support the hypothesis of an additional effect of mechanical damage using the rotating wire during MOCA. 5 Histological analysis of endothermally-treated GSVs after 1 to 2 months showed large empty areas covered with endothelium in all 8 cases.…”
Section: Discussionsupporting
confidence: 84%
“…All these complications seem to be related to thrombosis of the treated vein. Furthermore, the high postprocedural efficacy of foam sclerotherapy, which is reported as an occlusion of the treated vein, results from immediate thrombosis of such a vein, which precedes a slow process of inflammatory-driven fibrosis evoked by chemical irritation [3].…”
mentioning
confidence: 99%